Vertical jump fatigue does not affect intersegmental coordination and segmental contribution - Pereira, Gleber; Freitas, Paulo B. De; Barela, Jose A.; Ugrinowitsch, Carlos; Rodacki, André L. F.; Kokubun, Eduardo; Fowler, Neil E. (Universidade Estadual Paulista, 2014)
The aim of this study was to describe the intersegmental coordination and segmental contribution during intermittent vertical jumps performed until fatigue. Seven male visited the laboratory on two occasions: 1) the maximum vertical jump height was determined followed by vertical jumps habituation; 2) participants performed intermittent countermovement jumps until fatigue. Kinematic and kinetic variables were recorded. The overall reduction in vertical jump height was 5,5%, while the movement duration increased 10% during the test. The thigh segment angle at movement reversal significantly increased as the exercise progressed. Non-significant effect of fatigue on movement synergy was found for the intersegmental coordination pattern. More than 90% of the intersegmental coordination was explained by one coordination pattern. Thigh rotation contributed the most to the intersegmental coordination pattern, with the trunk second and the shank the least. Therefore, one intersegmental coordination pattern is followed throughout the vertical jumps until fatigue and thigh rotation contributes the most to jump height.

Fatiga salto vertical no afecta a la coordinación entre segmentos y la contribución segmentaria. El objetivo fue describir la coordinación entre los segmentos y sus contribuciones durante los saltos verticales realizadas hasta la fatiga. Siete sujetos visitaron laboratorio dos ocasiones: 1) determinó la máxima altura en el salto vertical y amistad con los saltos verticales; 2) participantes completaron saltos verticales contramovimento la fatiga. Se recogieron las variables cinemáticas y cinéticas. La altura del salto vertical disminuyó 5,5% y la duración del movimiento se incrementó 10%. El ángulo del muslo en instante de inversión del movimiento aumentó durante ejercicio. No hubo efecto de fatiga en sinergia de movimiento para la coordinación de movimientos. Más del 90% de coordinación entre sectores ha sido explicado por un patrón coordinativo. La rotación del muslo fue mayor contribuyente la coordinación de movimientos, seguido por tronco y piernas. En los saltos verticales realizados hasta la fatiga se mantiene coordinación entre segmentos y rotación del muslo tiene mayor contribución en altura del tacón.

Fadiga em salto vertical não afeta a coordenação intersegmental e contribuição segmental. O objetivo deste estudo foi descrever a coordenação entre segmentos e suas contribuições durante saltos verticais intervalados realizados até a fadiga. Sete indivíduos visitaram o laboratório em duas ocasiões: 1) foi determinada a altura máxima do salto vertical e realizada familiarização com saltos verticais; 2) participantes realizaram saltos verticais em contramovimento até a fadiga. Foram coletadas variáveis cinemáticas e cinéticas. A altura do salto vertical reduziu 5,5% e duração do movimento aumentou 10%. O ângulo da coxa no instante de reversão do movimento aumentou durante o exercício. A fadiga na sinergia do movimento não influenciou na coordenação intersegmental. Acima de 90% da coordenação entre segmentos foi explicada por um padrão coordenativo. A rotação da coxa foi o que mais contribuiu com o padrão coordenativo, seguido pelo tronco e perna. Portanto, em saltos verticais realizados até a fadiga, a coordenação intersegmental é mantida e a rotação da coxa tem maior contribuição na altura do salto.
Keywords: intermittent exercise; principal component analysis; psychomotor performance; exercício intervalado; análise do componente principal; desempenho psicomotor